Pengaruh CR, ROA, DER terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Variabel Moderasi - Qorry Tsaniatuzaima; Eny Maryanti (Owner : Riset dan Jurnal Akuntansi, 2022)
Based on the objectives of this research, including to find out the results of the test how much influence the Current Ratio (CR), Return on Assets (ROA) and Debt to Equity Ratio (DER) have on firm value, and the effect of Good Corporate Governance (GCG) as moderation the research method used is quantitative. The population is taken from food and beverage company data from 2018 to 2020. The sampling is purposive sampling. Initially the population of researchers was 78 companies, after passing the specified sample criteria, only 45 companies remained. The data analysis technique is Partial Least Square (PLS) including the SmartPLS 3 application. The results of the research : current ratio and return on assets have no effect on firm value. Debt to equity ratio has an effect on firm value. Current ratio and return on assets cannot be moderated by good corporate governance. Debt to equity ratio can be moderated by good corporate governance. The moderating variable in this study is the first one included in the moderating potential because the moderating effect 1 and the moderating effect 2 have no effect on the dependent variable. While the second type of moderation is included in pure moderation because the moderating effect 3 has an influence on the dependent variable, while the moderating variable does not affect the dependent variable.